Preliminary evaluation of a freeze dried mukteswar Newcastle disease vaccine - Ibrahim, A. Latif; Ungku Mohsin, Ungku Chulan; Babjee, A. Mustaffa (Persatuan Doktor Veterinar Malaysia, 1980)
The preparation of a freeze dried mukteswar Newcastle Disease vaccinc is described. Chicken which had been vaccinated toitli the ‘F’ Newcastle Disease vaccine and subsequently re-vaccinated with this vaccine were resistant when challenged either intranasally or intramuscularly or by contact with the virulent Newcastle Disease virus. Chickens revaccinated with this vacciue at 6 weeks old resisted challenge up to 20 weeks of age. The merits of the vacciuc is discussed